Comparative Study According to Absolute Power and Muscular Activity (EMG) between Leg and Arm Muscles for Weightlifting Trainees - Ghassan Adeeb Abdlhassan (Journal of Global Pharma Technology, 2018)
It is known that inside the exercises of maximum power there are trends and factors influential and for the purpose of verifying the extent of the effects of these factors in the maximum force had to go into these factors and to determine the reality, which comes in the forefront of the area of the cross section of the muscle, so researchers compared between the muscles of the arms and legs in terms of strength the absolute value of these two muscles in order to verify the returns of the maximum power and determine accurately. The main objectives of the research to identify the following:Identify the differences between the muscles of the limbs (legs - arms) according to the absolute power of weightlifters.The researchers selected a random sample of 6 students from the College of Physical Education and Sports Science / University of Baghdad. The researchers conducted tests of the maximum strength of the two men and arms on the research sample. The results were obtained and dealt with statistically using (SPSS).The most important conclusions were as follows:That the muscles of the arms of absolute strength higher than the muscles of the legs.Keywords: Absolute power, Muscular activity, Muscles and weightlifting.